Properties comparison between free and immobilized wheat esterase using glass fiber film - Ye, Lin; Liu, Xiang; Shen, Guang-Hui; Li, Shan-Shan; Luo, Qing-Ying; Wu, He-Jun; Chen, An-Jun; Liu, Xing-Yan; Li, Mei-Liang; Pu, Biao; Qin, Wen; Zhang, Zhi-Qing (International journal of biological macromolecules, 2019)
In this paper, the catalytic performance of non-purified esterase from wheat bran immobilized on glass fibre membrane carrier is established, the immobilization conditions observed were enzyme 1 mL, phosphate buffer 3 mL (pH 7.0), immobilization time 1 h, immobilization temperature 29 °C. After carrier functionalization some characteristics of immobilized enzyme were studied, the results showed that immobilized enzyme presenting improved characteristic than that of free enzyme. The optimum pH for free and immobilized enzymes were found to be 8 and 7, respectively. As for optimum temperature for free and immobilized enzymes were observed to be 30 °C and 40 °C, respectively. When the enzyme was immobilized on glass fibre membranes, its Km increased about 7 times. In addition, storage and thermal stability of the free wheat esterase were increased by as a result of membrane immobilization, after 12 days of storage, the immobilized enzyme still retained about 91.10% of its original activity at 4 °C, indicating a great potential in industrial application. [Display omitted] •The wheat esterase was immobilized on glass fiber film for the first time.•Enzymatic properties of immobilized wheat esterase are proposed.•Catalytic properties of wheat esterase changes of the presence of carrier.•Immobilized wheat esterase presenting improved characteristic than that of free enzyme.